Analisis Perkembangan Kognitif Anak Usia Dini di Kelompok Bermain Qurota A’yun Melalui Benda Konkret - Turiyah Turiyah (LPPM IAINU Kebumen, 2022)
This study aims to analyze the cognitive development of early childhood in the Qurota A'yun Gandrungmangu Cilacap Playgroup through concrete objects. This research is qualitative research with research subjects being school principals, teachers, and students of the Qurota A'yun Gandrungmangu Cilacap play group. The instruments in the research were interview sheets, observations, and documentation. Test the validity of the data using triangulation techniques. The data analysis technique uses the Miles and Huberman model which consists of four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: 1) the cognitive development of children in the Qurota A'yun Gandrungmangu play group has developed as expected; 2) through concrete objects such as color balls, puzzles, natural materials can develop early childhood cognitive abilities.